2017
DOI: 10.1016/j.ydbio.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

miR-27 regulates chondrogenesis by suppressing focal adhesion kinase during pharyngeal arch development

Abstract: Cranial neural crest cells are a multipotent cell population that generate all the elements of the pharyngeal cartilage with differentiation into chondrocytes tightly regulated by temporal intracellular and extracellular cues. Here, we demonstrate a novel role for miR-27, a highly enriched microRNA in the pharyngeal arches, as a positive regulator of chondrogenesis. Knock down of miR-27 led to nearly complete loss of pharyngeal cartilage by attenuating proliferation and blocking differentiation of pre-chondrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…Integrin-ECM interactions promote osteogenic differentiation while inhibiting chondrogenesis in mesenchymal stem cells (17). Increased FAK activation prevents chondrogenesis (39), and intrinsic FAK expression is actively down-regulated in developing chondrocytes (59), which we also confirmed in chondrogenic hBMSCs ( fig. S6A).…”
Section: Discussionsupporting
confidence: 76%
“…Integrin-ECM interactions promote osteogenic differentiation while inhibiting chondrogenesis in mesenchymal stem cells (17). Increased FAK activation prevents chondrogenesis (39), and intrinsic FAK expression is actively down-regulated in developing chondrocytes (59), which we also confirmed in chondrogenic hBMSCs ( fig. S6A).…”
Section: Discussionsupporting
confidence: 76%
“…There is some evidence to suggest that miRNA expression changed the across different species from miRNAs in many models of myocardial I/R injury, demonstrating the pivotal role of miRNAs in myocardial ischemic injury . It has been proposed that miR‐27 regulates cell differentiation in many diseases . It has conclusively been shown that miR‐27 may be involved in occurrence and development of atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…1,18 It has been proposed that miR-27 regulates cell differentiation in many diseases. 19,20 It has conclusively been shown that miR-27 may be involved in occurrence and development of atherosclerosis. 19 However, there were no reports on miR-27 acting a role in myocardial ischemic injury.…”
Section: Downregulated Expression Of Mir-27 In Myocardial Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence reveals that miRNAs are implicated in several physiological and pathological processes, such as inflammation, carcinogenesis, and chondrogenesis, though binding to the 3′UTR of target genes (Jiang, Wang, & Shi, ; Kara, Wei, Commanday, & Patton, ; Li et al, ; Shen et al, ). In particular, miR141‐3p is considered to regulate OA features including apoptosis, inflammation, neurogenesis, drug resistance, and development of the disease (Jiang et al, ; Jin et al, ; Li et al, ; Saha, Choudhury, & Ain, ; Shen et al, ; Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%